2012
DOI: 10.4236/jmmce.2012.114026
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heat Treatment on Al6061- Frit Particulate Composites

Abstract: In recent decades, aluminium alloy based metal matrix composites are used in several applications. Al6061 has been used as matrix material due to its good formability, excellent mechanical properties and etc., wide spectrum of the applications in industrial sectors. Inclusion of Frit particulates as reinforcement in Al6061 alloy material system improves its hardness and decrease in density. In the present investigation Al6061-Frit particulate composites were produced by 'VORTEX' method with varying weight perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…A liquid metallurgy route has been adopted to prepare the cast composites as described in our earlier works [9]. Al6061 has been chosen as the matrix alloy.…”
Section: Reinforcing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A liquid metallurgy route has been adopted to prepare the cast composites as described in our earlier works [9]. Al6061 has been chosen as the matrix alloy.…”
Section: Reinforcing Materialsmentioning
confidence: 99%
“…Use of TiO 2 as reinforcement in aluminum alloys has received little attention although it possess high hardness and modulus with superior corrosion resistance [4]. Of all the aluminum alloys, Al6061 is quite popular choice as a matrix material to prepare metal matrix composites owing to its better formability characteristics and option of modification of the strength of composites by adopting optimal heat treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the figure 3.5 shows that the increase in the weight percentage of MgO particulate it is found that significant improvement in hardness, it is due to presence of hard ceramic MgO particulate improves the hardness and wear resistance of Al LM13/MgO composite material [11][12][13][14][15]. …”
Section: Hardness Figure 35 Variation Of Hardness With Increase In Wmentioning
confidence: 99%
“…9,10 Activated carbon is one of a type of carbon processed to have low and small volume pores that increase adsorption due to the higher surface area available. 11 As per literature review, the Activated carbon surface area is in excess of 500m. 2,12,13 The density of activated carbon is 2100kg/m 3 .Compare to available reinforcement added with AA6061 activated carbon have some distinct advantages like readily available, cheap and good adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In that observation aluminium fly, ash composite has improved their mechanical properties by adding some suitable percentage of reinforcement. 5,6 In some other literature, there will be changes in mechanical properties by mixing reinforcements like SiC, Ti, Albite, graphite etc. 7,8 The tensile and compressive property was improved by adding AA6061 with different weight percentage of albite and graphite.…”
Section: Introductionmentioning
confidence: 99%